(untitled) (Global Scientific Review, 2023)
his research aims to apply ornaments using decoupage techniques to furniture at UD Mandiri Telaga Jaya. The type of research is R&D (research and development/) research with a qualitative approach . Data collection: observation, interviews, experiments, documentation. Data analysis: data reduction, data presentation, and verification. Research results: stages of applying ornaments using decoupage techniques to furniture: 1) analysis of potential, problems, and gathering information: a) strategic location; b) supporting transportation; c) woodpile; d) adequate buildings; e) building shop. All potential becomes UD Mandiri’s strength in facing competitors. The next problem with UD Mandiri is that consumers’ tastes for furniture with additional ornaments have not been met; 2) product design : the product uses drawers and chairs that are already available. The design process is used to determine tissue and napkin motifs and create designs for arranging furniture motifs; 3) design validation; 4) design improvements: adding ornamental motifs using painting techniques; 5) product trials; a) preparation of tools and materials; b) preparation of furniture; c) application of napkin wipes; d) adding ornaments to the edges of furniture using painting techniques using acrylic paint; e) applying varnish; f) research results . The application of tissue paper napkins using decoupage techniques as ornaments on furniture, chairs and drawers, has added to the aesthetic value of the furniture , making it an alternative for developing furniture ornaments at UD Mandiri Telaga Jaya